2013
DOI: 10.1002/ps.3465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solvent on the toxicity of dimethoate in a honey bee in vitro larval study

Abstract: Consideration of the solubility of the toxic reference and test items when designing studies is important. The use of higher rates of acetone in the present study more closely represents the true exposure of larvae to pesticides that are not highly soluble in diet. Published 2012. This article is a U.S. Government work and is in the public domain in the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…Studies on the exposure of bees during the larval stage through in vitro rearing tests also focus on this species (Aupinel et al 2007;Hendriksma et al 2011;Wilkins et al 2013;Tavares et al 2015). However, Kremen et al (2002), Del Sarto et al (2005) and Tomé et al (2015) highlighted the importance of native pollinators in the context of insecticide use in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the exposure of bees during the larval stage through in vitro rearing tests also focus on this species (Aupinel et al 2007;Hendriksma et al 2011;Wilkins et al 2013;Tavares et al 2015). However, Kremen et al (2002), Del Sarto et al (2005) and Tomé et al (2015) highlighted the importance of native pollinators in the context of insecticide use in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Additional sources of variation can occur from the composition of the pesticide formulations that are used. While different amounts of solvents used for toxicology analysis can affect the readout (Wilkins et al, 2013), pesticide adjuvants (other ingredients found in pesticide formulations that are thought to be inert) can also influence pesticide toxicity (Chen et al, 2019). An emerging interest is the potential for synergistic toxicity between multiple pesticides that are applied in combination.…”
Section: Pesticide Toxicology In Honey Beesmentioning
confidence: 99%
“…Assim, é evidente a importância da padronização de testes que envolvam abelhas em todas as idades, para que seja possível prever os potenciais prejuízos para a colônia como um todo, bem como atingir medidas mitigadoras dos efeitos sobre abelhas. (Oomen et al, 1992;Aupinel et al, 2007a;Hendriksma et al, 2012;Wilkins et al, 2013; Pilling et al, (2013) e Carreck e Ratnieks (no prelo) afirmam que os estudos conduzidos em condições de laboratório e em casas de vegetação tem evidenciado efeitos subletais em abelhas, através da exposição dos indivíduos a doses muito superiores àquelas registradas em campo Henry et al, 2012;Schneider et al, 2012; …”
Section: Protocolos Padronizados Existentes Para Estudos De Toxicidadeunclassified
“…Os estudos acerca da exposição de abelhas durante a fase larval, através de testes de criação in vitro, também enfatizam essa espécie Aupinel et al, 2007a;Hendriksma et al, 2012;Wilkins et al, 2013; …”
unclassified